Occurrence of the eucalypt leaf beetle, Cadmus excrementarius Suffrian (Coleoptera: Chrysomelidae: Cryptocephalinae), in Western Australia - Dos Anjos, N.; Majer, Jonathan; Loch, A. (2002)
The chrysomelid beetle Cadmus excrementarius has recently been observed as a pest in south-western Australian blue gum (Eucalyptus globulus ssp globulus) plantations. The insect was first recorded from Western Australia in 1904 and has since been found at over 30 different locations in the State. Seven host species from the genera Eucalyptus and Corymbia have been recorded in Westem Australia. Most records of C. excrementarius adults were in the months of January to March. The insect mainly occurs on blue gums in the area bounded by the jarrah (Eucalyptus marginata) forest, where it may persist on flooded gum (Eucalyptus rudis) and to a lesser extent marri (Corymbia calophylla). E . marginata appears to be a less preferred host for C. excrementarius beetles, because its leaves were significantly less consumed than those of E. rudis and C. colophylla. Some observations on the natural history and predators of this beetle are presented.